A Benefit Analysis of Electric Vehicle Battery Swapping and Leasing Modes in China. Issue 6 (2nd June 2016) - Zhang, Xingping; Rao, Rao
ABSTRACT: This article discusses three most potential operators in the electric vehicle (EV) market of China, including power companies, battery manufacturers and gasoline enterprises. We propose five commercial modes of battery swapping and leasing service (BSLS) and analyze their benefits. The simulation results indicate that oil companies are the least competitive operators, whereas battery manufacturers are the best. It is unadvisable for operators to acquire batteries via leasing. The sensitivity analysis indicates that the increase in vehicle weight, gasoline price, the quantity of EVs and V2G electricity price will expand operators' profit respectively, while the increase in discount rate works inversely.